Reproductive and sexual rights of women: ground reality - Singh, Sunayana; Kumar, Mukesh; Sharma, Subrat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Inequality exists in different societies of the world. Discrimination and exploitation are done based on caste, color, creed, gender, region and religion by mighty people. However, international bodies like United Nations and International Commission of Human Rights are very sensitive about the human rights. Reproductive and sexual rights are also part of human rights. The most sufferers of this discrimination and sexual exploitation are women. Woman suffers in silence because her exploiters are generally close ones. The study was done in rural areas of Bharatpur, Rajasthan, to investigate the awareness status of reproductive and sexual rights of women. Methods: Questionnaires pertaining to the awareness of contraceptive choice, age of pregnancy, planned/unplanned and delivery place, family size and sexual life was prepared. Woman of 20 to 40 years of age volunteered to participate for this research. Results: Majority of women were not having the basic knowledge of pregnancy, contraceptive choices. 60% of women got pregnant before reaching to the age of 20 and second pregnancy occurring between 21 to 25 of age. Majority of women had unplanned pregnancy and delivered the baby at home. 2-5 kids were per family of studied group. 65-70% of their husband treated their wives as a sex object and slaves. They tortured their wife during sexual act. These women were not aware of their reproductive and sexual rights Conclusions: This study shows early marriage, pregnancy. Majority of husband tortured their wives during sex (or forced) sex and treated them sex slaves. Reproductive and sexual rights are distant dream for women in rural areas of India.